Do climate anxiety and pro-environmental behaviour affect one another? : a longitudinal investigation : a thesis presented in partial fulfilment of the requirements for the qualification of Doctor of Clinical Psychology at Massey University, Auckland, New Zealand - McLean, Tamara Alice (Massey University, 2024)
Anthropogenic climate change poses a serious threat to psychological wellbeing. One particular negative emotional response gaining scholarly attention is climate anxiety: anxious feelings arising from climate change, even among people not yet personally impacted by this global environmental crisis. Research suggests that climate anxiety might be implicated in pro-environmental behaviour. Specifically, climate anxiety may motivate individuals to act in ways that, if widely adopted, could mitigate the damage caused by climate change. Furthermore, there is a common assumption that these sustainable behaviours will alleviate climate anxiety, creating a mutually beneficial cycle where pro-climate actions increase and distressing anxiety is eased. However, these ideas are not well supported by empirical and theoretical evidence. This study aimed to test the hypotheses that 1) climate anxiety causes pro-environmental behaviour to increase over time, and 2) pro-environmental behaviour causes climate anxiety to decrease over time. A sample of 700 Australian and New Zealand adults was recruited via the online research platform Prolific and surveyed monthly on five occasions. Data were analysed using a random intercept cross-lagged panel model, which controlled for stable, between-person differences while focusing on dynamic within-person changes over time. The study found no evidence of a causal relationship between climate anxiety and pro-environmental behaviour. Higher levels of climate anxiety at one wave were not significantly associated with higher levels of pro-environmental behaviour at the following wave, and higher levels of pro-environmental behaviour at one wave were not significantly associated with lower levels of climate anxiety at the next wave. Furthermore, levels of climate anxiety were very low across the sample, indicating that climate anxiety, experienced at a level that causes clinically significant emotional and cognitive impairment, is relatively rare. These findings suggest that climate anxiety is unlikely to have the helpful side effect of increasing an individual’s engagement in pro-environmental behaviour, but neither will it deter a person from taking action. Moreover, taking action is unlikely to reduce climate anxiety. Further scholarship is needed to investigate climate anxiety and its complex relationship with pro-environmental behaviour.
Keywords: climate anxiety, CCAS, pro-environmental behaviour, climate change, random intercept cross-lagged panel model; Climatic changes; Psychological aspects; New Zealand; Australia; Environmentalism; Environmental psychology; Anxiety; 520302 Clinical psychology